Developing English Printed Material on Theme of Plant for Early Young Learners at Paud Terpadu Joy Kids Makassar - Hilalia, Nur; Kamsinah, Kamsinah; Nurpahmi, Sitti (Institut Agama Islam Negeri Kudus, 2020)
Based on a preliminary study conducted in PAUD Terpadu Joykids Makassar, it was found that the material provided for students in introducing English vocabulary based on theme is still limited. In this case, the researcher intended to develop thematic English material for students. This study was Research and Development adapting ADDIE model that consists of Analysis, Design, Development, Implementation and Evaluation. In developing the material the researcher concerned on developing “plant” theme material. There were 1 teacher, 2 experts and 20 students involved in this research. This study found out the need of students at PAUD Terpadu Joykids over English material. The data of students need then become the inventory need in designing and developing the material. Moreover, the material consisted of English vocabulary integrated with the theme, number, picture, simple sentence, and artwork.